Differentiation of Pluripotent Stem Cells Into Thymic Epithelial Cells and Generation of Thymic Organoids: Applications for Therapeutic Strategies Against APECED - Provin, Nathan; Giraud, Matthieu (Frontiers in Immunology, 2022)
The thymus is a primary lymphoid organ essential for the induction of central immune tolerance. Maturing T cells undergo several steps of expansion and selection mediated by thymic epithelial cells (TECs). In APECED and other congenital pathologies, a deficiency in genes that regulate TEC development or their ability to select non auto-reactive thymocytes results in a defective immune balance, and consequently in a general autoimmune syndrome. Restoration of thymic function is thus crucial for the emergence of curative treatments. The last decade has seen remarkable progress in both gene editing and pluripotent stem cell differentiation, with the emergence of CRISPR-based gene correction, the trivialization of reprogramming of somatic cells to induced pluripotent stem cells (iPSc) and their subsequent differentiation into multiple cellular fates. The combination of these two approaches has paved the way to the generation of genetically corrected thymic organoids and their use to control thymic genetic pathologies affecting self-tolerance. Here we review the recent advances in differentiation of iPSc into TECs and the ability of the latter to support a proper and efficient maturation of thymocytes into functional and non-autoreactive T cells. A special focus is given on thymus organogenesis and pathway modulation during iPSc differentiation, on the impact of the 2/3D structure on the generated TECs, and on perspectives for therapeutic strategies in APECED based on patient-derived iPSc corrected for AIRE gene mutations.